2010
DOI: 10.1002/pssa.200983773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deposition temperature on the physical properties of RF magnetron sputtered Ag–Cu–O films with various Cu to Ag ratios

Abstract: Thin films of Ag-Cu-O were deposited on glass substrates held at various temperatures in the 303-523 K range by RF magnetron sputtering of Ag 90 Cu 10 , Ag 80 Cu 20 and Ag 70 Cu 30 , and elemental copper and silver targets in an oxygen partial pressure of 2 Â 10 À2 Pa and sputtering pressure of 4 Pa. The deposited films were characterised by energy dispersive X-ray analysis, X-ray diffraction (XRD), atomic force microscopy, UV-Vis-NIR spectroscopy and employing four-point probe method. The atomic ratio of Cu/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The electrical resistivity of pure silver was 1.6 × 10 −6 Ωcm. The Ag 2 O films formed by RF magnetron sputtering at oxygen partial pressure of 2 × 10 −2 Pa was 3 × 10 −3 Ωcm [20]. Ravi Chandra Raju et al [21] reported that the electrical resistivity of pulsed laser deposited AgO films was close to 2 × 10 5 Ωcm.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical resistivity of pure silver was 1.6 × 10 −6 Ωcm. The Ag 2 O films formed by RF magnetron sputtering at oxygen partial pressure of 2 × 10 −2 Pa was 3 × 10 −3 Ωcm [20]. Ravi Chandra Raju et al [21] reported that the electrical resistivity of pulsed laser deposited AgO films was close to 2 × 10 5 Ωcm.…”
Section: Resultsmentioning
confidence: 99%
“…Petitjean et al [10,11] reported the effect of annealing temperature on the decomposition-and structurerelated properties of reactively sputtered Ag 2 Cu 2 O 3 films deposited with Ag 50 Cu 50 and with Ag 60 Cu 40 sputter targets. Uthanna et al [12] reported the influence of deposition temperature on the structural and optical properties of Ag 2 Cu 2 O 3 films formed by RF magnetron sputtering. Tseng et al [13] deposited Ag-doped Cu 2 O films (0-50 at.…”
Section: Introductionmentioning
confidence: 99%
“…Pititjean et al [10][11][12] studied the effect of oxygen flow rate on the structure and properties of pulsed DC sputtered Ag-Cu-O films deposited using Ag 60 Cu 40 target. The effect of deposition temperature on the structural and optical properties of RF magnetron sputtered Ag 70 Cu 30 target was systematically studied [13]. In this investigation, thin films of Ag 2 Cu 2 O 3 films were formed on glass substrates by RF magnetron sputtering of mosaic Ag 70 Cu 30 target at different oxygen partial pressures.…”
Section: Introductionmentioning
confidence: 99%